Copper(II) adsorption by waste tea leaves and coffee powder - Tan, W. T. (Universiti Pertanian Malaysia, 1985)
The consumed coffee powder and tea leaves of local produce were found to be able to remove substantial amounts of Cu(II) ions from aqueous solution. The characteristics of Cu(II) uptake on these beverage waste were systematically investigated. It was found that the Cu(II) uptake was dependent on pH, metal concentration, physical nature of substrate and ionic strength. Competing ions/molecules such as Pb(II) and surfactant such as Triton X-lOa interfere in the uptake of Cu(II). The degree of uptake increases with pH and the pH range for maximum uptake was found to be 5 - 7 for both wastes. Metal concentration dependent assumed a Langmuir Isotherm. The results obtained were found to be consistent with the mechanisms that Cu(II) uptake was due to specific ion adsorption via ch elation and some degree of ion-exchange reaction.